CORPORATE RESPONSIBILITY IN PROVIDING WAGES BELOW THE MINIMUM WAGE - Ida Hanifah (Proceeding International Seminar of Islamic Studies, 2023)
Wages are one of the important stimuli for employees in a company. This does not mean that it is the wage rate that is the main driver, the wage rate is only the main driver so that the wage rate is not sufficient to adequately meet the needs of the workers. employer's orders. Individuals, entrepreneurs, legal entities or other entities and for their services in the work concerned receive wages or other forms of compensation. In other words, workers are called workers if they carry out work in an employment relationship and on orders from other people by receiving wages or other forms of compensation. The criminal sanctions imposed in this law are in the form of imprisonment and fines.The minimum wage policy also aims as a tool to fight poverty and encourage Indonesia's economic development with fair and competitive wages. Salaries are adjusted annually to the upper and lower limits of the minimum wage for the relevant area. If the employer unreasonably violates the wages paid for the work, in this case paying less than the minimum wage, the employer can be classified as a criminal offense according to the Labor Code. Roeslan Saleh writes in his book Hanafi Amrani: According to the provisions of criminal law, actions that are prohibited are referred to as criminal acts (which can be punished) or minor violations.